2012
DOI: 10.1021/ef201814v
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Double-Swirled Non-premixed Syngas Flames by Planar Laser-Induced Fluorescence

Abstract: Experimental measurements are carried out on a non-premixed model combustor, equipped with a double-swirled syngas burner. Mixtures of H 2 , CO, and CO 2 with appropriate contents are used to simulate corresponding syngas used in a practical gas turbine combustor. Planar laser-induced fluorescence (PLIF) of OH radical measurement is adopted to identify main reaction zones and burnt gas regions as well. Together with the temperature and emission measurements during the exhaust section, some important characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… In comparison with the N 2 and H 2 O diluents, CO 2 dilution has a better effect in reducing the flame temperature. Ge et al measured the flame characteristics of the H 2 /CO/CO 2 non-premixed flame using OH-PLIF and discussed the flame structure changes with N 2 dilution. It was found that the structure of the double flame front appears at the root of the non-premixed syngas flame, and the change in the CO/H 2 ratio enabled the position of the flame root to move and compress the thickness of the reaction zone.…”
Section: Introductionmentioning
confidence: 99%
“… In comparison with the N 2 and H 2 O diluents, CO 2 dilution has a better effect in reducing the flame temperature. Ge et al measured the flame characteristics of the H 2 /CO/CO 2 non-premixed flame using OH-PLIF and discussed the flame structure changes with N 2 dilution. It was found that the structure of the double flame front appears at the root of the non-premixed syngas flame, and the change in the CO/H 2 ratio enabled the position of the flame root to move and compress the thickness of the reaction zone.…”
Section: Introductionmentioning
confidence: 99%
“…The syngas of the gas turbine for this technology mainly consists of H 2 , CO and a small amount of CH 4 , etc. [3]. Although the heat value of syngas is lower than that of natural gas, its combustion equilibrium temperature is higher due to its hydrogen-rich characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated gasification combined cycle (IGCC) technology combined with carbon capture and storage (CCS) technology is a very competitive approach for use in clean coal technology . The syngas of the gas turbine fuel for this technology mainly consists of H 2 , CO, and a small amount of CO 2 , CH 4 , and N 2 . Syngas gas turbine technology must overcome two challenges: one is combustion safety, and the other is combustion pollution control.…”
Section: Introductionmentioning
confidence: 99%
“…1 The syngas of the gas turbine fuel for this technology mainly consists of H 2 , CO, and a small amount of CO 2 , CH 4 , and N 2 . 2 Syngas gas turbine technology must overcome two challenges: one is combustion safety, and the other is combustion pollution control. For security considerations, to prevent the problems of autoignition and flashback, a diffusion flame is used for IGCC syngas gas turbine combustion.…”
Section: Introductionmentioning
confidence: 99%